ROLE OF PAX-5 TRANSCRIPTION FACTOR IN PATHOGENESIS OF BRONCHIAL ASTHMA - V. N. Mineev (SPb RAACI, 2014)
Abstract. Expression characteristics of transcription factor PAX-5 (paired box 5) are considered for different clinical variants of bronchial asthma (BA). Low levels of PAX-5 expression may be a reason for progression into a severe allergic asthma, whereas higher levels of PAX-5 expression may represent a significant factor leading to development of non-allergic bronchial asthma. Initiation of IgE production is supposed to be a less important PAX-5 function in BA pathogenesis, than prevention of B-cell-to-plasmocyte differentiation. Further investigations of PAX-5 properties and its co-operations with other transcription factors may provide a promising path in further research of BA pathogenesis.